Untoward outcomes of successful chronic subdural hematoma evacuation, cortical blindness and brain stem stroke: A Case series - Rakesh Singh Raghuvanshi; Rakesh Gupta; Piyush Panchariya; Ajay Chaudhary (Asian Journal of Medical Sciences, 2024)
Chronic subdural hematoma (CSDH) is one of the most commonly encountered emergencies in neurosurgery practice. Burr hole with drainage of hematoma has been a time-tested standard treatment with good results and in itself a simple procedure to relieve patient clinical status. However, apparently simple surgery may at times have an unexpected surgical outcome of bilateral vision loss. All bilateral CSDHs should be treated diligently with early recognition of any visual deterioration in post-operative phase if any and due to possible interventions to be offered to the patients for prevention of permanent vision loss.